Numerical experiments for improvement in mesoscale simulation of Orissa super cyclone - MANDAL , M.; MOHANTY, U. C. (MAUSAM, 2006)
& 29 vDrwcj] 1999 dks mM+hlk ds rV ij vk;k egkpØokr mM+hlk ds vc rd ds bfrgkl dk lcls izpaM rwQku Fkk ftldh 250 fd-eh- izfr ?kaVk dh rhoz xfr okyh iouksa us jkT; ds 12 rVh; ftyksa dks rgl&ugl dj MkykA rwQku ds LFky ls Vdjkus ds i'pkr~ 36 ?kaVs ls Hkh vf/kd le; rd iouksa dh izpaMrk cuh jghA bl rwQku ls tku eky dk dkQh uqdlku gqvkA yxHkx 10]000 yksxksa dh tkusa xbZA bl v/;;u esa rwQku ds eslksLdsy izfr:Ik dks csgrj cukus ds fy, dqN egRoiw.kZ igyqvksa dh tk¡p gsrq O;kid la[;kRed iz;ksx fd, x, gSaA bu igyqvksa esa xSj nzoLFkSfrd xfrd] fun’kZ {kSfrt foHksnu vkSj egRoiw.kZ izR;{k izfØ;kvksa ds izkpyhdj.k 'kkfey gSaA rwQku dk 5 fnolh; izfr:Ik ¼123 ?kaVksa ds yxkrkj lekdyu½ rS;kj djus ds fy, eslksLdsy fun’kZ ,e- ,e- 5 dk mi;ksx fd;k x;k gSA blesa le:ih foHksnu ¼30 fd-eh-½ vkSj le:ih le; J`a[kyk ds lkFk nzoLFkSfrd ¼,p-,l-½ rFkk xSj nzoLFkSfrd ¼,u- ,l-½ xfrdksa ds lg;ksx ls rwQku ds izfr:i esa xSj nzoLFkSfrdrk ds izHkko dh tk¡p dh xbZ gSA bl fof/k ls rwQku vkSj fo’ks"k :Ik ls bldh rhozrk dk xSj nzoLFkSfrd xfrdksa ds lkFk lgh izfr:i.k gksrk gSA xSj nzoLFkSfrd xfrdksa ds lkFk 90 fd-eh-] 60 fd-eh- vkSj 30 fd-eh- ds foHksnuksa ij rwQku dk izfr:i.k djrs gq, fun’kZ dh laof/kZr {kSfrt foHksnu dh egRrk dh tk¡p dh xbZ gS vkSj rwQku ds izfr:i.k esa bldk izR;{k izHkko ns[kk x;k gSA egRoiw.kZ izR;{k izfØ;k okys diklh laogu xzgh; ifjlhek Lrj ¼ih- ch- ,y-½ vkSj fofdj.k gsrq fun’kZ esa miyC/k izkpyhÑr ;kstukvksa ds csgrj lEHkkO; leUo; dk irk yxkus ds fy, la[;kRed iz;ksx Hkh fd, x,A lh- lh- ,e- 2 fofdj.k izkpyhÑr ;kstuk lesr xzsy diklh laogu vkSj gk¡x&isu ih- ch- ,y- ;kstuk ds lkFk leUo;u okyh ;kstuk ds vU; ijhf{kr ;kstukvksa dh rqyuk esa lcls csgrj ifj.kkeksa dk irk pyk gSA The super cyclone that crossed Orissa coast on 29 October 1999 was the most intense storm in the history of Orissa with 12 coastal districts of the state were battered by winds reaching 250 kmph. The fury of winds continued for more than 36 hours after landfall of the storm. The storm caused huge damage to properties and nearly 10,000 people lost their lives. In the present study, extensive numerical experiments are conducted to investigate some important aspects that may lead to the improvement in mesoscale simulation of the storm. The aspects that are addressed here include non-hydrostatic dynamics, model horizontal resolution and parameterization of important physical processes. The mesoscale model MM5 is used to produce 5-day simulation of the storm. The influence of non-hydrostaticity is investigated by simulating the storm with hydrostatic (HS) and non-hydrostatic (NS) dynamics at same resolution (30 km) and with same time step. The storm, in particular its intensity is better simulated with non-hydrostatic dynamics. The importance of increasing model horizontal resolution is investigated by simulating the storm at 90 km, 60 km and 30 km resolutions with non-hydrostatic dynamics and found to have perceptible impact in simulation of the storm. Numerical experiments also are conducted to find the best possible combination of the parameterization schemes available in the model for the important physical processes cumulus convection, planetary boundary layer (PBL) and radiation. The combination of Grell cumulus convection and Hong-Pan PBL scheme along with CCM2 radiation parameterization scheme is found to provide the best result compared to the other schemes tested.